Peningkatan Kemampuan Interpretasi Electrocardiogram (ECG) Perawat Dengan Pembelajaran Pelatihan Dan Multimedia Di RSUD Dr. Soeratno Sragen - Akhmad Rifai; Dwi Sulistyowati (Poltekkes Kemenkes Surakarta, 2017)
Abstract: Level Of Ability Of Nurses, ECG Interpretation. American Heart Association (AHA) in 2011, recorded more than 1.000.000 people have heart attacks every year, half died from the heart attack and in Europe figures reach 20,000-40,000 CHD patients than 1,000,000 population. In Indonesia in 2002 with acute myocardial infarction disease is the first cause of death with a mortality rate of 220,000 (14%). The purpose of this study to determine the level of ability to interpret ECG nurse in RSUD dr. Soeratno Gemolong Sragen. This research is an experimental approach to Pre-TestPost Test Group design. through research hypothesis testing. The study population was a nurse amounted to 50 respondents divided into two groups. 30 respondents as the treatment group and 20 respondents as the control group. Statistical tests on the group in pairs using the nonparametric Wilcoxon test and unpaired pad groups using the Mann-Whitney test. Based on the results of the Wilcoxon test can be concluded that the 30 respondents who do the training interpretation of ECG by means of training and training using the modules can be drawn the conclusion that the majority of nurses had good knowledge in terms of ability to interpret ECG with p-value 0.001, which means there are significant differences between before and after doing the training. While the results of the Mann-Whitney test the difference between training and training in how to use the module p-value 0.001, which means there is a significant difference training by way of training and training in how to use the module.